(untitled) (Indian Journal of Animal Production and Management, 2024)
Frustration arising from lack of social contact and inconsistent training method, insufficient roughages, erratic management practices and different bedding material leads to redirected behaviour and vices in stabled horses. Further there was a need to assess the relation between behaviour and vices related to prevalence of many stereotypes and redirected behaviour i.e., weaving, tongue rolling, resting in the stable corner, soil consuming, wood chewing and cribbing. The aim of current research work was to establish the importance of bedding on behaviour of horses. Fifteen each of privately owned, mares and stallions were selected for the study. They were kept in the boxes in which they were observed for a minimum of four weeks. Recordings were made between 10:00 to 12 AM and 5:00 to 7:00 PM. There was an increase in the prevalence of abnormal behaviour (P<0.0001) when the bedding type other than straw was used (P<0.0001) and the amount of fibre in the diet was decreased (<40%). Results showed that there were significant differences in other behaviours like resting in the stable corner (P<0.0001), tongue rolling (P<0.0001), weaving behaviour (P<0.0001), yawning behaviour (P<0.0001), wood chewing (P<0.0005) and cribbing (P<0.0008). No significant differences were found with soil (P<0.558) and faeces consumption (P<0.3251) behaviour. The amount of time spent on exercise and time spent outside the stable did not appear to be related to performance of abnormal behaviour and vices of horses. It was concluded that the providing adequate bedding material can influence the behaviour and vices in stabled horses.